Co-firing of levator palpebrae and masseter muscles links the masticatory and oculomotor system in humans - Houcheng, Liang; Jinxin, Song; Di, Shen; Ying, Qiao; Jingdong, Zhang (Journal of biomedical research, 2015)
Simultaneous co-firing of the levator palpebrae （LP） and pterygoid muscles were recorded in Marcus Gann Syndrome （MGS） patients in early clinical studies. ＂Release hypothesis＂ proposed an intrinsic masticatory oculo- motor neural circuit and this kind circuit, which, however, has been observed only in amphibian. On the other hand, congenital miswiring hypothesis has overwhelmed other interpretations. However, the same phenomenon visualized in MGS cases was unveiled in human subjects without any sign of congenital oculomotor disorder. To further study co-firing of the upper eyelid and jaw muscles, we applied non-invasive EMG recording of the upper eyelid and ipsilateral masseter muscle belly in nine healthy volunteers. LP activity was determined initially by looking upward and active retraction of upper eyelid with head fixed. Then, dual channel inputs from upper eyelid and masseter muscle was recorded during tooth occlusion motivated by isometric masseter muscle contraction without jaw and face moving. The EMG recorded from upper eyelid when the subjects retracted eyelid with head fixed exhibited the same pattern as that collected during tooth occlusion, but the pattern was completely different from EMG of active eye closure. This reflects tooth occlusion evoked LP activity. Then, simultaneous co-firing of the LP and masseter muscle was recorded simultaneously during tooth occlusion without jaw movement. Finally, the aforemen- tioned co-firing was recorded when the subjects conducted rhythmic occlusion and synchronous EMG from both muscles was acquired. In conclusions, humans may also have an intrinsic masticatory oculomotor circuit and release hypothesis may apply, at least, to some cases of MGS.